DIFFERENCES AND SIMILARITIES IN THE DIVISION OF INHERITANCE LAW ACCORDING TO ISLAMIC LAW AND JAVANESE CUSTOMARY LAW IN INDONESIA IN A COMPARATIVE STUDY OF LAW, so that - Nurmala, Leni; Koni, Yoslan (RADJA PUBLIKA, 2022)
The acquisition of property through inheritance is a form of legal ownership and is justified by Allah SWT. The Qur'an and Hadith have also provided explanations regarding the parties who are entitled to become heirs along with the amount or amount of distribution of inheritance. However, in everyday life in society, the distribution of inheritance often creates its own problems, the distribution of inheritance is vulnerable to conflict and prone to disputes between parties who are entitled to become heirs. The method used in this paper is the normative legal research method. Namely the type of research method that is doctrinal in nature and comes from research sources from the library. In research, it is necessary to have library sources that are relevant to the subject being studied. In Indonesia, the applicable inheritance law is still not uniform. This is because there are different laws of inheritance, including civil inheritance law, customary inheritance law, and Islamic inheritance law. However, this paper only focuses on the division of inheritance law according to customary inheritance law and Islamic inheritance law. In Indonesia, there are very diverse customary laws, so this research is more directed to Javanese customary law of inheritance which adheres to the term sepikul segendongan, namely that boys get twice the share of girls. The principle of sepikul-segendong implies that men and women both get the same inheritance rights, but each share is different, the men who are considered to have a bigger role and responsibility get more shares (sepikul) than men. women (segendong), however, as Muslims, they should obey and submit to the provisions stipulated in Islamic law.